2008
DOI: 10.1002/pits.20321
|View full text |Cite
|
Sign up to set email alerts
|

Assessing giftedness in children: Comparing the accuracy of three shortened measures of Intelligence to the Stanford–Binet Intelligence Scales, Fifth Edition

Abstract: This study examined the accuracy of three shortened measures of intelligence: the WoodcockJohnson Tests of Cognitive Ability, Third Edition Brief Intellectual Ability (WJ III COG BIA) score; the Stanford-Binet Intelligence Scale, Fifth Edition Abbreviated IQ (SB5 ABIQ); and the Kaufman Brief Intelligence Test IQ Composite (K-BIT) in predicting giftedness as assessed by the SB5 Full Scale IQ score (SB5 FSIQ). Participants were 202 third grade students who were individually administered the SB5, WJ III, and K-BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…The difference we observed in mean performance in the present study suggests that it may be prudent for psychologists who test students identified as ELLs for gifted program eligibility purposes to use any of the other seven measures whose scores we examined statistically, rather than the Stanford-Binet V, at least until more data become available. This finding is consistent with results reported for Stanford-Binet V testing for gifted program eligibility determination among mainstream gifted learners (Minton & Pratt, 2006;Newton et al, 2008).…”
Section: Nonverbal Content and Score Equalitysupporting
confidence: 94%
See 2 more Smart Citations
“…The difference we observed in mean performance in the present study suggests that it may be prudent for psychologists who test students identified as ELLs for gifted program eligibility purposes to use any of the other seven measures whose scores we examined statistically, rather than the Stanford-Binet V, at least until more data become available. This finding is consistent with results reported for Stanford-Binet V testing for gifted program eligibility determination among mainstream gifted learners (Minton & Pratt, 2006;Newton et al, 2008).…”
Section: Nonverbal Content and Score Equalitysupporting
confidence: 94%
“…Much research on identification practice in gifted education settings has been based in a correlational perspective that examines the relationships among and between aptitude tests and other measures used in the identification process (Ashman & Vukelich, 1983;Borland, 1978;Minton & Pratt, 2006;Nevo & Sela, 2003;Newton, McIntosh, Dixon, Williams, & Youman, 2008;Rizza, McIntosh, & McCunn, 2001;Simpson, Burns, Seidman, Montgomery, & Sellers, 2002;Sweetland, Reina, & Tatti, 2006;Thompson, Diamond, McWilliam, Snyder, & Snyder, 2005). Although helpful in discerning patterns and potential relationships among measures, it is all too often the case in practice that correlations drawn from narrowly defined settings are mistaken for causal relationships.…”
Section: Aptitude (Iq) Testing In Gifted Identificationmentioning
confidence: 97%
See 1 more Smart Citation
“…The abbreviated version includes a singular verbal-based test and non-verbal test producing an abbreviated battery IQ (ABIQ). Newton, McIntosh, Dixon, Williams, and Youman (2008) found a high correlation between ABIQ and FSIQ (r = .71, p < .001), therefore, participants with either ABIQ scores or FSIQ scores were included in the current study.…”
Section: Stanford-binet Intelligence Scales-5th Edition (Sb5)mentioning
confidence: 98%
“…Así por ejemplo Ramsden y colaboradores (2011) señalan como existen variaciones en las puntuaciones de niños y jóvenes que podrían relacionarse con cambios en la estructura cerebral debidos a diferentes factores tales como la edad, la estimulación, el sexo, etc…, o sea relacionables con la plasticidad cerebral. Sea este u otro el motivo, el caso es que se señalan cierto número de factores que intervienen en la variabilidad de las puntuaciones obtenidas a lo largo del tiempo por los tests más reputados, tales como el WISC (Lohman y Korb, 2006) o K-Bit -aunque este se haya mostrado como el test breve que mejor predice la sobredotación intelectual- (Mervis et al, 2012;Newton, McIntosh, Dixon, Willians y Youman, 2008) La cuestión de la estabilidad de puntuaciones tiene una importancia considerable pues precisamente en la estabilidad …”
unclassified